Type-I clathrates of K7.69(2)Cu2.94(6)Ge43.06(6) and Rb8Ag2.79(4)Ge43.21(4)1. Issue 66 (19th July 2015) - Zhang, Hui; Xu, Xuguang; Li, Wei; Mu, Gang; Huang, Fu-Qiang; Xie, Xiao-Ming
<x xml:space="preserve">Abstract</x> Type-I clathrates of K7.69(2)Cu2.94(6)Ge43.06(6) and Rb8Ag2.79(4)Ge43.21(4) are successfully synthesized.